2010
DOI: 10.1073/pnas.0910012107
|View full text |Cite
|
Sign up to set email alerts
|

Neural differentiation of human induced pluripotent stem cells follows developmental principles but with variable potency

Abstract: For the promise of human induced pluripotent stem cells (iPSCs) to be realized, it is necessary to ask if and how efficiently they may be differentiated to functional cells of various lineages. Here, we have directly compared the neural-differentiation capacity of human iPSCs and embryonic stem cells (ESCs). We have shown that human iPSCs use the same transcriptional network to generate neuroepithelia and functionally appropriate neuronal types over the same developmental time course as hESCs in response to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
724
6
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 920 publications
(762 citation statements)
references
References 35 publications
27
724
6
2
Order By: Relevance
“…iPSC show either equal performance to ESC or in some cases inferior performance, especially when comparing the efficiency of their turnover into differentiated cells. Surprisingly, taking into account their degree of characterization-that is, the measures taken to work with ''good quality'' iPSC, or (although here the data is much more scarce) transgene free cells-there seems to be no correlation with the differentiation efficiency or the quality of the final cells [52]. This aspect of occasional iPSC low performance can perhaps be explained by the fact that the differentiation protocols are mainly established with ESC.…”
Section: Differentiation Potential Of Ipscmentioning
confidence: 88%
“…iPSC show either equal performance to ESC or in some cases inferior performance, especially when comparing the efficiency of their turnover into differentiated cells. Surprisingly, taking into account their degree of characterization-that is, the measures taken to work with ''good quality'' iPSC, or (although here the data is much more scarce) transgene free cells-there seems to be no correlation with the differentiation efficiency or the quality of the final cells [52]. This aspect of occasional iPSC low performance can perhaps be explained by the fact that the differentiation protocols are mainly established with ESC.…”
Section: Differentiation Potential Of Ipscmentioning
confidence: 88%
“…For instance, HSF1 primarily form forebrain neurons whereas HSF6 predominantly produce hindbrain, cervical and thoracic neurons (Wu et al, 2007). The bias of neural differentiation seems getting much more significant in hiPSCs, regardless of how the hiPSCs was derived (Hu et al, 2010). The variable potency of different lines of PSCs may be a result of the native heterogeneity of the starting cells that were chosen for expansion, which calls for identification of novel marks that could characterize those cells with real pluripotency.…”
Section: Revisiting the Pluripotency Of Hescsmentioning
confidence: 99%
“…Ebert et al [20] established iPSC lines from a type 1 SMA patient and showed that these iPSCs exhibited reduced capacity to form mature motoneurons in vitro. As high intrinsic variability in differentiation exists among different iPSC lines [21][22][23], the reduced capacity to form motoneurons by the SMA iPSCs may be attributed to clonal variation rather than the underlying genetic defect. Establishment of iPSC lines from other SMA patients with similar phenotypes would address this concern.…”
Section: Introductionmentioning
confidence: 99%